2023
DOI: 10.1088/1402-4896/acf3b1
|View full text |Cite
|
Sign up to set email alerts
|

Control effect of superhydrophobic grooves on flow-induced noise generated by flow around cylindrical shell at large Reynolds number

Chen Niu,
Qikai Qin,
Yongwei Liu
et al.

Abstract: Flow-induced noise is an important factor affecting the quiet performance of underwater vehicles. Superhydrophobic surfaces are an emerging technology for underwater vehicles. In this study, a superhydrophobic surface is innovatively applied to the flow-induced noise control of underwater cylindrical shells. Alternating no-slip and no-shear surfaces are used to simulate the superhydrophobic surface with spanwise superhydrophobic grooves so that the flow regime and flow-induced noise of a no-slip cylinder are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The results showed that superhydrophobic surfaces could delay flow separation, control wake-shedding vortex size, and significantly reduce flow-induced noise by managing vortex shedding and reducing fluctuation pressure. These surfaces also modified radiation directivity at various frequencies, providing fresh perspectives for underwater vehicle noise control [193].…”
Section: Applications Of Biomimetic Noise Reductionmentioning
confidence: 99%
“…The results showed that superhydrophobic surfaces could delay flow separation, control wake-shedding vortex size, and significantly reduce flow-induced noise by managing vortex shedding and reducing fluctuation pressure. These surfaces also modified radiation directivity at various frequencies, providing fresh perspectives for underwater vehicle noise control [193].…”
Section: Applications Of Biomimetic Noise Reductionmentioning
confidence: 99%